Estimation of spawning population of pond smelt Hypomesus nipponensis by the egg production method in Lakes Shinji and Nakaumi, Japan - IMAI, Chifumi; FUJIKAWA, Yuji (Bulletin of the Japanese Society of Fisheries Oceanography, 2016)
Pond smelt catch in Lake Shinji has been at a low level since 1994. The population has not yet recovered, nevertheless gill-net catch has been banned in spawning season at the river mouth of Hii River, the major spawning ground. We carried out population estimation by the egg production method for fundamental information on further stock management policy. Pond smelt attaches their adhesive eggs to sands or gravels at the bottom. Mean number of pond smelt eggs sampled from 0–6 cm layer of sandy bottom was 88.4 per unit area of 0.05 m2 by egg sampling survey in the 2004 spawning season. Total area of major spawning ground in Hii River was 242,987 m2. Total number of eggs in 0–6 cm layer of sandy bottom was estimated as 429,601,016. Number of spawning females was calculated as 39,247 individuals, and biomass of both sexes was estimated as 861 kg. Moreover, 2.25 fold eggs were deposited to a depth of 0–15 cm layer compared with 0–6 cm. Spawning population was estimated as 1,937 kg, using the value.